P122 Celiac disease associated with depression in adolescents. (June 2019) - Rácz, Orsolya-Adrienn; Tita, Georgia; Pârvan, Alexandru; Predescu, Elena; Căinap, Simona
Abstract : Introduction: Celiac disease is an immune-mediated systemic disorder elicited by gluten which causes malabsorption and small-bowel mucosal inflammation in genetically susceptible individuals. Although the gastrointestinal tract is the target of autoimmune insult, celiac disease is also associated with extra-intestinal problems: autoimmune disorders, malignancies, dermatologic conditions, rheumatologist conditions, neurologic and psychiatric disorders. The psychological symptoms are one of the most interesting and unexpected presentations, which may be the result of nutrient malabsorption or increased levels of proinflammatory cytokines. Case report: We present the case of a 15 year old adolescent girl with a history of autoimmune thyroiditis on replacement therapy with levothyroxine, who was hospitalised because of behaviour disorders and oligobradimenorrhea. On clinical examination the patient presented drowsiness, sudden behavioural changes, learning problems, bradylalia and a tendency to isolate herself. Blood tests showed positive anti-TG2 antibodies (>10x normal) and EMA antibodies. HLA typing was also performed and was positive for HLA-DQ2 cis: DQA1*05 - DQB1*02 - DRB1*03. On the psychiatric consult she was diagnosed with a minor depressive syndrome. She was immediately started on a gluten free diet. Although she showed low compliance to the diet on the follow-up examinations, removing gluten resulted in positive effects on the psychiatric symptomatology. We would also like to add that the patient refused the oesophagogastroduodenoscopy and psychological counselling. Conclusion: Recent studies have shown an association between celiac disease and psychiatric conditions, especially depression. Medical personnel should be aware of this atypical presentation of the disease in order to correctly diagnose and treat celiac disease. Also, psychiatric patients who are resistant to traditional therapy should be investigated for celiac disease in case they also present symptoms of CD or if a positive family history exists.